Organic Luminophores Exhibiting Bimodal Emissions of Fluorescence and Room‐Temperature Phosphorescence for Versatile Applications. Issue 41 (30th October 2020) - Zhuo, Chaozheng; Ouyang, Mi; Li, Chengjian; Zhang, Yujian; Cao, Feng; Pan, Guoxiang; Lv, Chunyan; Zhang, Xia; Sun, Jingwei
Abstract: Organic luminophores exhibiting both fluorescence and phosphorescence at room temperature are attractive but rare, due to the limited design strategies of room temperature phosphorescence (RTP) molecules. Here, the construction of electron donor‐acceptor‐donor (D−A−D) structure, which can afford multiple and powerful intermolecular interactions and electronic communications, is proposed as an effective method to achieve RTP. Two compounds NBCM and PBCM were designed with different electron withdrawing groups. Both exhibit efficient RTP with long lifetimes of 558 and 482 ms, as well as switchable luminescence from cyan or white to yellow, respectively. The stronger charge transfer effect and better crystallization capacity of NBCM are account for its superior RTP performance in relative to PBCM. Besides, the incorporation of pyridine endows NBCM with a special response to trifluoroacetate acid and a reversible on/off conversion of emissions. These features of NBCM pave the way to its promising applications in antifake security, encryption, fingerprint imaging and sensors. Abstract : Dual emissive luminophores with both fluorescence and room temperature phosphorescence are obtained, which exhibit switchable emission with/without UV illumination. Owing to the D−A−D molecular structure, which afford rich intermolecular interactions and electronic communications, such luminescent properties still remain even in microcrystalline forms. Thus, the compounds could be practically used in versatile applications for preventing counterfeits, encryption and fingerprint imaging.